Gliosis, misfolded protein aggregation, and neuronal loss in a guinea pig model of pulmonary tuberculosis - Latham, Amanda S.; Geer, Charlize E.; Ackart, David F.; Anderson, Isla K.; Vittoria, Kaley M.; Podell, Brendan K.; Basaraba, Randall J.; Moreno, Julie A. (Frontiers in Neuroscience, 2023)
Tuberculosis, caused by Mycobacterium tuberculosis infection, is an ongoing epidemic with an estimated ten million active cases of the disease worldwide. Pulmonary tuberculosis is associated with cognitive and memory deficits, and patients with this disease are at an increased risk for Parkinson’s disease and dementia. Although epidemiological data correlates neurological effects with peripheral disease, the pathology in the central nervous system is unknown. In an established guinea pig model of low-dose, aerosolized Mycobacterium tuberculosis infection, we see behavior changes and memory loss in infected animals. We correlate these findings with pathological changes within brain regions related to motor, cognition, and sensation across disease progression. This includes microglial and astrocytic proliferation and reactivity. These cellular changes are followed by the aggregation of neurotoxic amyloid β and phosphorylated tau and, ultimately, neuronal degeneration in the hippocampus. Through these data, we have obtained a greater understanding of the neuropathological effects of a peripheral disease that affects millions of persons worldwide.